A Sociological Study on Socio and Economic Condition of Child Labour in Nepal - Sherpa, Furgel (A Bi-annual South Asian Journal of Research & Innovation, 2024)
This article offers a comprehensive analysis of child labour in Nepal, emphasizing the socio-economic factors that sustain this pervasive issue. It delves into the historical evolution of child labour, the legal frameworks governing childhood, and the interplay of poverty, illiteracy, and cultural norms that perpetuate the exploitation of children. The 2015 earthquake is identified as a critical event that intensified child labour due to its profound socio-economic repercussions. The article also examines the regional and industrial distribution of child labour, revealing a multifaceted problem deeply rooted in Nepal’s socioeconomic fabric. While legislative measures, such as the Child Labour Act, are recognized, the persistent challenges in enforcement, particularly within the informal sector, are highlighted. The article concludes by advocating for a holistic and sustained approach to eradicate child labour, ensuring the protection of children’s rights and fostering a society that prioritizes their development and well-being.